2018
DOI: 10.1186/s12894-018-0320-0
|View full text |Cite
|
Sign up to set email alerts
|

Intravescical prostatic protrusion is a predictor of alpha blockers response: results from an observational study

Abstract: BackgroundTo investigate the efficacy of tamsulosin in patients with lower urinary tract symptoms (LUTS) and benign prostatic enlargement (BPE) with intravesical prostatic protrusion (IPP). Ultrasound measurement of the IPP has been previously described as an effective instrument for the evaluation of benign prostatic obstruction (BPO) and could help in clarifying the role of alpha-blockers in patients with (BPE).MethodsPatients with BPE and LUTS were enrolled in this observational study. Intravesical prostati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 27 publications
2
13
1
Order By: Relevance
“…The standard critical value of PV =80 mL was chosen for the prostatectomy (18). The IPP was the important parameter to assess BPH (19). IPP, IPPT, IPPV, IPPI and IPPS of PV >80 mL group were significantly higher than those in PV <80 mL group in our study.…”
Section: A B C Dmentioning
confidence: 55%
“…The standard critical value of PV =80 mL was chosen for the prostatectomy (18). The IPP was the important parameter to assess BPH (19). IPP, IPPT, IPPV, IPPI and IPPS of PV >80 mL group were significantly higher than those in PV <80 mL group in our study.…”
Section: A B C Dmentioning
confidence: 55%
“…Topazio et al found that IPP was significantly and inversely correlated with treatment success in patients with lower urinary tract symptoms (LUTS) and BPH under alphablockers therapy. IPP can be used as a predictor of alpha-blockers response [15]. A recent study indicated that IPP was a good predictor of clinically significant BOO due to BPH [16].…”
Section: Discussionmentioning
confidence: 99%
“…Also, prostates were selected for size and lack of focal pathology to increase the chance of having a homogenous sample. These measures were taken to account for the higher likelihood of biological variability among human prostates [1517] than among kiwifruits [18]. Tenth, examinations in this study were consequently limited to large prostates with benign prostate hyperplasia and kiwifruits of similar volume.…”
Section: Discussionmentioning
confidence: 99%
“…Lately, commercially available kiwifruits ( Actinidia deliciosa ) have been introduced as a phantom model to substitute for human prostates in dedicated MR examinations including T2WI, DWI with ADC maps, and magnetic resonance spectroscopy [14]. Unlike human prostates, which are known for biological variability [1517], kiwifruits traded in the European Union are regulated to limit biological differences [18]. Thus, experiments comparing different MRI techniques involving kiwifruits instead of human prostates should emphasise technical differences and limit effect modification by biological variability.…”
Section: Introductionmentioning
confidence: 99%